Problem Pengembangan Kreativitas Hakim di Tengah Intervensi Kekuasaan dan Mafia Peradilan (Bercermin pada Pemikiran Filsafat Hukum Roscoe Pound) - Syafi'i SJ, Ahmad (Fakultas Syariah IAIN Purwokerto, 2009)
Roscoe Pound stated that law must be functioned as a social control and social engineering so there should be a space for them to be more creative on applying the laws.Almost all of law holders have the duty realizing the ideal of law completely. Among other law holders the position of the judge is special. The judge basically is the representation of God in the world to uphold the law and justice. Nevertheless placing the judge as law maker is not always easy, because they are only one of practical caretakers of law which their independence and integrity is often covered by some internal and external interests.